Implementasi Nilai PAI dalam Mendorong Perilaku Peduli Gizi dan Ketahanan Pangan - Siti Muzayyanah; Oliefia Fitriani; Ni'matul Muawanah (Jurnal Pendidikan, Kepelatihan, Olahraga, dan Kesehatan, 2025)
Efforts to improve nutrition awareness and food security are multidimensional challenges that require synergy between education, culture, and religious values. Islamic Religious Education (PAI) plays a strategic role in building nutrition awareness and responsible consumption behavior through teachings on balance, cleanliness, moderation, and trustworthiness in food management. This literature review aims to analyze the relationship between PAI values ​​and nutrition awareness and food security behavior, as well as their implementation in educational and community contexts. This study reviewed various sources such as scientific journals, textbooks, and relevant research reports. The results indicate that PAI values ​​such as tawazun (balance), taharah (cleanliness), amanah (trustworthiness), gratitude, and ishraf (anti-waste) contribute significantly to establishing healthy consumption patterns, avoiding excessive or unhealthy food consumption, and encouraging the wise use of food resources. The implementation of PAI in formal education can be achieved through the integration of nutrition materials into learning, the promotion of healthy eating habits in schools, and character building through teacher role models. Socially, PAI values ​​can strengthen the movement for halal, clean, and nutritious food, as well as community participation in maintaining family food security. This study confirms that Islamic Religious Education (PAI) can serve as an ethical foundation for building sustainable nutrition and food security awareness behaviors. Therefore, integrating Islamic Religious Education (PAI) into nutrition education and food management is a crucial step in creating a healthy, productive, and character-based generation.